HARMONY OF NATIONAL AND UNIVERSAL SPIRITUAL VALUES - Khudaynazarov Samad Khudayberdievich (American Journals Publishing, 2022)
The article is devoted to the actual problems of education of the culture of interethnic relations. The harmonious combination of the universal and the national is of particular importance against the background of increasing globalization processes around the world.
Keywords: tolerance, harmony, spirituality, globalization, humanism, universal processes, culture.